IN SILICO STUDY OF SILDENAFIL DERIVATIVES ADULTERANT AFFINITIES TOWARDS PDE5 ENZYME AND SYNTHESIS OF NEW SILDENAFIL DERIVATIVES QUALIFIED AS REFERENCE SUBSTANCE CANDIDATES - yulianti, Tanti
Since the United States Food and Drug Administration (US FDA) approved the use of sildenafil as the first drug of choice for the treatment of erectile dysfunction (ED), the drug has been transformed into a lifestyle-drug, that it is also for use under normal conditions to increase the duration of erection. On the other hand, the limitation of sildenafil use through prescription only, have made sildenafil increasingly difficult to obtain freely. This condition has an impact on the emergence of drug crime, namely the illegal use of sildenafil and or its derivatives in herbal products and health supplements intended to increase male stamina. The involvement of street chemistry and drug designers in conducting research and illegal production of sildenafil derivative compounds, clearly hinders laboratory testing to support the law enforcement process. Not less than 50 sildenafil derivatives have been identified in various commercially available herbal products and health supplements. Based on the literature search, studies of the pharmacological and safety effects of these sildenafil derivative compounds on human health have not been reported. Likewise, anticipatory law enforcement efforts cannot be carried out optimally, due to limitations and difficulties in obtaining appropriate reference standard required to conduct evidence through laboratory testing. This dissertation study aims to obtain the potential affinities of various sildenafil-derived compounds identified as adulterants in health supplement products as part of the risk assessment process of their hazard properties and to obtain new reference substance candidates of sildenafil derivedcompounds. Sildenafil interact with phosphodiesterase type-5 (PDE5) enzyme in the catalytic region and inhibit the catalytic activity of this enzyme as the target of action. Based on these facts, it can be assumed that those all sildenafil derivative compounds will also act with the same mechanism. Using in silico study, 50 sildenafil derivedcompounds were tested against the PDE5 enzyme. The in silico study was carried out through molecular docking (MD) and molecular dynamic simulation (MDS) using sildenafil as the comparison. Through MD step, the essential ligand functional groups, amino acid residues of the target protein, and type of interactions/chemical bonds formed will be obtained. The position of the ligand obtained through MD study was used as the input file for MDS. In the MDS, the movement of the ligand at the binding site of the target protein is carried out for a certain time and the interaction energy can be calculated which is expressed as binding free energy (DG), as a quantitative parameter to assess the affinity strength of the ligand-target interaction occurs. New sildenafil-derived compounds was created by considering its potential affinity for the PDE5 enzyme based on the presence of pharmacophores in the molecular structure and the likelihood of its ease of synthesis. The synthesis of those new sildenafil-derived compounds carried out through common organic reactions for sildenafil production. Confirmation of the structure of the synthesis product was demonstrated through an instrumental measurement techniques, particularly nuclear magnetic resonance spectroscopy for proton and carbon-13 (1 H- and 13C-NMR), as well as high-resolution mass spectroscopy (MS). Those substances following characterization measuremet by various instrumentation, which are : FTIR, Spectrofotometer UV/Vis, TLC, HPTLC, and DSC for identification; HPLC for impurity testing; and assignment value for its quantification used. Based on MD finding, 50 sildenafil-derived compounds were interacted with the catalytic site of the PDE5 enzyme and showing the DG value ranging from -36.5 kJ/mol to -57.4 kJ/mol. 36 ligands was identified to bind with PDE5 spesificly by hydrogen bond between atom in pyrazolopyrimidine and Gln817 from PDE5 enzyme, with 34 among of those were having the DG value more negative than sildenafil, indicating stronger affinity potency compared to sildenafil. The remaining 14 ligands form hydrogen bond with others amino acid residue or interact through hydrophobic interaction only in the catalytic site of PDE5 enzyme. The 50 sildenafil derived-compounds as ligands demonstrate structural stability in PDE5 enzyme's catalytic region through MDS. The DG of the 50 ligands were calculated using molecular mechanics Poisson Boltzmann surface are (MMPBSA) calculation method. The results were in the range of -38.54 kJ/mol for the SA07 ligand to -212.4 kJ/mol for SA27. Among 50 ligand-PDE5 enzyme complexes, due to their similarities in orientation, conformation and interactions formed in ligandPDE5 complexes with that of sildenafil revealed that SA04, SA08, and SA30 were demonstrated the higher affinities compared to sildenafil with the DG values of - 179.42 kJ/mol, -176.16 kJ/mol and -144,71 kJ/mol, respectively. Based on these results, the three sildenafil derivatives were predicted to have hazard potencies similar to or more than sildenafil. The four new sildenafil derived-compounds, which were: NSA-1, NSA-2, NSA-3, and NSA-4 were successfully synthesized with the yield of 80, 68, 61, and 31%, respectively. The confirmation of their structure were conducted by 1 H- and 13C-NMR as well as HRMS measurements. The characterization measurement result of those compounds using various instrumentation as FTIR, Spectrofotometer UV/Vis, TLC, HPLC and DSC for identification and impurity examination, and the assigned values calculation have showed that those substance were fulfilled the requairement of reference standard candidate for identification and impurity testing. The assigned resulted in 98,88% (NSA-1); 98,05% (NSA-2); 96,06% (NSA-3); and 99,07% (NSA-4), respectively. Parallelly, 4 new sildenafil derived-compounds were applied in MD and MDS. The DG value and the formation of specific hydrogen bond with Gln817 were used to evaluate the interaction of ligand towards PDE5 during specific length time. NSA- 3 and NSA-4 with the DG value of respectively, -118.15 kJ/mol and -115.65 kJ/mol, showed affinity potency toward PDE5 enzyme similar to that of sildenafil.